Marital Social Skills: A review of the Brazilian literature (Brazilian Journal of Behavioral and Cognitive Therapy, 2017)
This study aims to characterize a national production on marital social skills (MSS) and to identify possible gaps and opportunities for future research. It was held an initial literature survey on the portal of dissertations and theses of CAPES and after in the databases Scielo, Lilacs, Pepsic. As a result, nine studies composed the document databases on MSS,and the results were pointed out in the categories (a) theoretical; (b) applied; (c) characterization and/or correlations; (d) the construction, adaptation and validation of instruments. The analysis of these studies showed the main contributions of these studies to consolidate the area, including the concept of MSS, the construction of specific tools to assess these skills, and relations between MSS and other variables like marital satisfaction, locus of control, religious affiliation, and behavior problems in children. Finally, some questions for future researches on MSS are discussed.
Keywords: marital social skills; social skills; marital relationship; marriage; interpersonal relations